(untitled) (Моделювання, керування та інформаційні технології, 2025)
This paper presents the development and evaluation of a mathematical model of the small hydropower plant (SHPP Plavisko), focusing on transient hydraulic phenomena during typical and emergency operational states. The model, created using modular hydraulic and turbine components, simulates the dynamic response of the system under various conditions, including start-up, normal shutdown, generator trip, and emergency closures. The results of numerical simulations are evaluated in terms of pressure transients, turbine rotational speed, and overall system safety. The findings provide valuable insights into the hydraulic design and operational safety of small-scale hydroelectric installations